2010
DOI: 10.2174/092986710792064992
|View full text |Cite
|
Sign up to set email alerts
|

Materials Degradation in PVC Medical Devices, DEHP Leaching and Neonatal Outcomes

Abstract: Polymeric materials play a key role in the production of medical and clinical devices thanks to their special features such as flexibility, easy processing and good price/performance ratio. Among the different polymeric matrixes, one of the most used is Poly(vinyl chloride) (PVC). At room temperature PVC is hard and brittle, thus great amounts (40-50%) of phthalate esters that act as plasticizers are added to the polymer to make it flexible and appropriate for medical use. Di-(2-ethylhexyl)-phthalate (DEHP) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 0 publications
1
43
0
5
Order By: Relevance
“…They contained an average of 34% (w/w) DEHP. Most of the studies related to the plasticizer used in PVC medical products reported DEHP as the principal plasticizer being used [6,28], but no reliable statistics available on the quantity of phthalate used in such devices. Ruzickova et al [29] performed an exhaustive study in various European countries on the 48 medical devices -ranging from blood storage bags, injection sets, infusion and nutrition sets to tubing and masks -made of PVC plastics and found that DEHP used in such devices varied between 17% and 41% by weight.…”
Section: Discussionmentioning
confidence: 99%
“…They contained an average of 34% (w/w) DEHP. Most of the studies related to the plasticizer used in PVC medical products reported DEHP as the principal plasticizer being used [6,28], but no reliable statistics available on the quantity of phthalate used in such devices. Ruzickova et al [29] performed an exhaustive study in various European countries on the 48 medical devices -ranging from blood storage bags, injection sets, infusion and nutrition sets to tubing and masks -made of PVC plastics and found that DEHP used in such devices varied between 17% and 41% by weight.…”
Section: Discussionmentioning
confidence: 99%
“…-трансплантація серця або в коронарній хірур-гії шунтування артерій (сумарна доза); -масивне вливання крові при травмі пацієнта; -переливання у дорослих, під час процедури ЕКМО [13][14][15][16].…”
Section: метаболізм і токсичність Dehpunclassified
“…Most of the studies related to the plasticizer used in PVC medical products reported DEHP as the principal plasticizer being used [56]. An exhaustive study conducted in various European countries on the 48 medical devices -ranging from blood storage bags, injection sets, infusion and nutrition sets to tubing and masks -made of PVC plastics showed that DEHP content in such devices varied between 17 and 41% by weight [57].…”
Section: Clinical Studiesmentioning
confidence: 99%